“I don’t like Mondays”: weekdays in a long dream series - Schredl, Michael (International journal of dream research, 2025)
Whereas many dream studies focus on topics like dream characters and social interaction, the present analysis of a long dream series (N = 14,233 dreams) analyzed the occurrence of weekdays in dreams. Interestingly, there was a clear preferences of weekend days (Saturday, Sunday) compared to workdays (hence the title of the article). Moreover, work-related topics were significant more likely to occur in dreams with workday references compared to dreams with weekend references. The high occurrence of weekend days in dream might be associated with a higher salience of weekend-related activities. To summarize, studying “mundane” dream aspects like time of the day, weekdays, seasons and so on might be helpful in developing a more elaborated version of the continuity hypothesis.
Gesehen am 07.04.2025